Studi Biofisik pada Lanskap Hutan Rawa Gambut di Taman Nasional Sebangau: Kasus di Resort Mangkok - Muhammad Abdul Qirom; Wawan Halwany; Dony Rahmanadi; Agustinus Panusunan Tampubolon (Jurnal Ilmu Pertanian Indonesia, 2019)
Fire and illegal logging are main causes of peat swamp forest (PSF) degradation. Degradation causes biotic and abiotic changes of PSF. This reasearch was designed to collect data on description of species composition, carbon stock, soil physical factors, and soil macrofauna as indicators of changes in land condition due to PSF degradation. This research was conducted on degraded PSF area caused by fire and illegal logging. Sample plots were located based on the distance from the river i.e., <1.5; <4; and <10 km. Parameters measured included species composition of the stands and their ecological indices, carbon stock potention, soil physical condition (density), and soil macrofauna diversity. Research results showed that all of the parameters in those three locations were not significantly different. Based on those conditions, the main causes of degradation gave the same effects (biotic and abiotic changes) in the very ranged area with 10 km distances. These results were caused by the condition that all parameters measured were very sensitive to changes occurred in all experimental location.